Insights from teaching sustainable business models using a MOOC and a Hackathons - Jan Jonker; N. E. D. Faber (Journal of Business Models (JOBM), 2019)
We provide two teaching approaches, developed to teach sustainable business modeling to Bachelor and Master students. First, we present a MOOC on developing "new business models" focusing on practitioners in society. Second, we describe an approach in which students develop sustainable business models using a Hackathon as the teaching format.
Keywords: 650; Sustainable Business Models; Circular Economy; Social Inclusivity; MOOC; Hackathon